2007
DOI: 10.1093/gerona/62.12.1420
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Community-Based Multifactorial Intervention on Falls and Fall Risk Factors in Community-Living Older Adults: A Randomized, Controlled Trial

Abstract: A community-based multifaceted intervention was effective in improving balance, mobility, and leg strength, all known fall risk factors. Although the incidence of falls was lower, the confidence interval included the possibility of no intervention effect on falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
0
21

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 43 publications
4
109
0
21
Order By: Relevance
“…This was in agreement with Andersen et al, [40] who declared that patients may have weakness of the extensors and flexors at the ankle and of knee flexors with preservation of strength of the knee extensors and of muscles at the wrist and elbow. The distribution of muscular weakness confirmed that a distal neuropathic process is the cause of the impaired motor performance.…”
Section: Discussionsupporting
confidence: 92%
“…This was in agreement with Andersen et al, [40] who declared that patients may have weakness of the extensors and flexors at the ankle and of knee flexors with preservation of strength of the knee extensors and of muscles at the wrist and elbow. The distribution of muscular weakness confirmed that a distal neuropathic process is the cause of the impaired motor performance.…”
Section: Discussionsupporting
confidence: 92%
“…낙상을 예방하기 위한 중재는 근력강화운동, 음악과 함께 하는 좌식운동, 유연성 및 균형운동, 스트레칭 및 점진적 율동운동, 태극 운동, 탄성밴드를 이용한 운동 (Liu & So, 2008;Nelson et al, 2004;Rejeski et al, 2008;Shumway-Cook et al, 2007)과 교육, 환경수정요법 과 영양보충요법 등 (Clemson et al, 2004;Mahoney et al, 2007;Tinetti, Richman, & Powell, 1990 …”
unclassified
“…Most falls prevention studies in community dwelling older people have delivered the intervention in the primary care setting, in which the interventions are delivered by staff working in the community, and with general practitioners providing the medical intervention 28 The consensus appears to be that the components of a successful falls prevention intervention are strength and balance training, home hazards assessment and medical/medication review; the setting in which these components are delivered is of less importance, as long as it is acceptable to the intended participants.…”
Section: Setting For Interventionsmentioning
confidence: 99%